Pelayanan Pemerintah Berbasis Konsep Smart City Studi Kasus : Pelayanan Pemerintah Kota Yogyakarta berbasis Smart Environment - Lubna Salsabila; Sahat Sianturi (LPPM Universitas Putera Batam, 2023)
The smart environmental policy of the city of Yogyakarta as one aspect of the smart city is the focus of research. Apart from that, how the government can implement green waste as an aspect of the smart environment and use qualitative descriptive research methods. The research results reveal that the Yogyakarta City Government in running its government and serving its people is in accordance with the indicators of the smart environment concept. This means that the government's efforts to implement the program have been successful and comprehensive. The program covers 3 aspects of smart environmental indicators, namely green planning and green design, green open space and green waste. For the waste management program, the Yogyakarta city government is considered successful in reducing waste and managing its waste, this is proven by the innovation of the Waste Bank as a solution to the large amount of waste in the city. from Yogyakarta. However, of course the implementation of smart city in the city of Yogyakarta must also continue to develop and be sustainable so that the performance of the Yogyakarta city government must be improved and the active participation of the people of Jogjakarta to create a new innovation to be able to realize a smart city that fulfills all aspects other than the smart environment aspect.